2015
DOI: 10.1111/1556-4029.12769
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Forensic Autopsy in 120 Cases of Medical Disputes Among Different Levels of Institutional Settings

Abstract: Despite advances in medical science, the causes of death can sometimes only be determined by pathologists after a complete autopsy. Few studies have investigated the importance of forensic autopsy in medically disputed cases among different levels of institutional settings. Our study aimed to analyze forensic autopsy in 120 cases of medical disputes among five levels of institutional settings between 2001 and 2012 in Wenzhou, China. The results showed an overall concordance rate of 55%. Of the 39% of clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Emerging studies have focused on the intensified doctor-patient relationship in China [12]. Several previous studies have also shown the clinic-pathological discrepancy in separate regions in China [3, 13]. All these studies has technically failed to analyze the time trends of medical disputes and diagnostic discrepancy underlying disputed cases over a lengthy period.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have focused on the intensified doctor-patient relationship in China [12]. Several previous studies have also shown the clinic-pathological discrepancy in separate regions in China [3, 13]. All these studies has technically failed to analyze the time trends of medical disputes and diagnostic discrepancy underlying disputed cases over a lengthy period.…”
Section: Discussionmentioning
confidence: 99%
“…The settlement of medical disputes is generally handled through consultation between doctors and patients. If the consultation fails, the parties may apply for mediation to the health administration department or directly file a civil lawsuit to the people’s court [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is regarded as the interaction between a care provider and a care user. [1] Medical disputes generally refer to dissent between patients' families and medical care providers on medical results and reasons causing such results [2] . The doctor-patient relationship is generally harmonious in developed countries such as Britain and the United States as these countries own relatively comprehensive legal system and medical insurance system.…”
Section: Introductionmentioning
confidence: 99%